Evaluating Alternative Basic Income Mechanisms. A Simulation for European Countries - Ugo Colombino (Statistics Norway, Research Department, 2009)
We develop and estimate a microeconometric model of household labour supply in five European countries representative of different economies and welfare policy regimes: Denmark, Italy, Norway, Portugal and United Kingdom. We then simulate, under the constraint of constant total net tax revenue, the effects of various hypothetical tax-transfer reforms which include alternative versions of a Basic Income mechanisms. We produce various indexes and criteria according to which the reforms can be ranked. The exercise can be considered as one of empirical optimal taxation, where the optimization problem is solved computationally rather than analytically.
Keywords: C25; H24; H31; I38; 330; Basic Income; Minimum Guaranteed Income; Models of Labour Supply; Tax Reforms; Welfare Evaluation; Optimal Taxation